The Genesis of fiction: modern novelists as biblical interpreters - Wright, Terence R. (Ashgate, 2007)
Wrestling with the book of Genesis -- Adam, Eve, and the serpent : Mark Twain -- Cain and Abel : John Steinbeck -- From the flood to Babel : Jeanette Winterson -- The sacrifice of Isaac : Jenny Diski -- Rachel and her sisters : Anita Diamant -- Joseph and his brothers : Thomas Mann